Thrombospondin-1 expression and modulation of Wnt and hippo signaling pathways during the early phase of Trypanosoma cruzi infection of heart endothelial cells - Ashutosh Arun; Kayla J. Rayford; Ayorinde Cooley; Tanu Rana; Girish Rachakonda; Fernando Villalta; Siddharth Pratap; Maria F. Lima; Nader Sheibani; Pius N. Nde (Public Library of Science (PLoS), 2022)
The protozoan parasite, Trypanosoma cruzi, causes severe morbidity and mortality in afflicted individuals. Approximately 30% of T. cruzi infected individuals present with cardiac pathology. The invasive forms of the parasite are carried in the vascular system to infect other cells of the body. During transportation, the molecular mechanisms by which the parasite signals and interact with host endothelial cells (EC) especially heart endothelium is currently unknown. The parasite increases host thrombospondin-1 (TSP1) expression and activates the Wnt/β-catenin and hippo signaling pathways during the early phase of infection. The links between TSP1 and activation of the signaling pathways and their impact on parasite infectivity during the early phase of infection remain unknown. To elucidate the significance of TSP1 function in YAP/β-catenin colocalization and how they impact parasite infectivity during the early phase of infection, we challenged mouse heart endothelial cells (MHEC) from wild type (WT) and TSP1 knockout mice with T. cruzi and evaluated Wnt signaling, YAP/β-catenin crosstalk, and how they affect parasite infection. We found that in the absence of TSP1, the parasite induced the expression of Wnt-5a to a maximum at 2 h (1.73±0.13), P< 0.001 and enhanced the level of phosphorylated glycogen synthase kinase 3β at the same time point (2.99±0.24), P<0.001. In WT MHEC, the levels of Wnt-5a were toned down and the level of p-GSK-3β was lowest at 2 h (0.47±0.06), P< 0.01 compared to uninfected control. This was accompanied by a continuous significant increase in the nuclear colocalization of β-catenin/YAP in TSP1 KO MHEC with a maximum Pearson correlation coefficient of (0.67±0.02), P< 0.05 at 6 h. In WT MHEC, the nuclear colocalization of β-catenin/YAP remained steady and showed a reduction at 6 h (0.29±0.007), P< 0.05. These results indicate that TSP1 plays an important role in regulating β-catenin/YAP colocalization during the early phase of T. cruzi infection. Importantly, dysregulation of this crosstalk by pre-incubation of WT MHEC with a β-catenin inhibitor, endo-IWR 1, dramatically reduced the level of infection of WT MHEC. Parasite infectivity of inhibitor treated WT MHEC was similar to the level of infection of TSP1 KO MHEC. These results indicate that the β-catenin pathway induced by the parasite and regulated by TSP1 during the early phase of T. cruzi infection is an important potential therapeutic target, which can be explored for the prophylactic prevention of T. cruzi infection. Author summary Trypanosoma cruzi, the causative agent of Chagas disease, is now considered a global health threat in all industrialized regions of the world. About 30% of infected individuals will develop cardiac pathology. The molecular mechanisms by which the parasite signals and infect host cells to cause pathology remain to be elucidated. We showed that host thrombospondin-1 (TSP1) is essential for T. cruzi infection since cells deficient in TSP1 are poorly infected by the parasite. In this study, we challenged mouse heart endothelial cells from wild type and TSP1 KO mice and evaluated the importance of TSP1 in Wnt/β-catenin signaling, β-catenin/YAP colocalization and how it can be exploited to regulate parasite infectivity. The parasite activated Wnt/β-catenin signaling pathway and nuclear β-catenin/YAP colocalization. In TSP1 KO MHEC (absence of TSP1), the parasite induced a continuous increase in nuclear translocation and colocalization of β-catenin/YAP. These results suggest that during the early phase of T. cruzi infection, TSP1 regulates β-catenin/YAP interaction. Inhibition of the Wnt/β-catenin pathway in WT MHEC led to a significant reduction of parasite infectivity. The level of parasite infection of the pretreated WT cells was as low as that of TSP1 KO MHEC. Our studies show that the β-catenin pathway is an important therapeutic target for T. cruzi infection.